Analisis Filogenetik Cyprinus carpio Ruang Lingkup Asia Timur Dan Eropa Berdasarkan Genom Mitokondria - Putra, Erik Nanda; Razak, Abdul; Sumarmin, Ramadhan (Metamorfosa: Journal of Biological Sciences; Vol 8 No 1 (2021)DO - 10.24843/metamorfosa.2021.v08.i01.p18, 2021)
Carp (Cyprinus carpio L.) is one of the oldest and most commercially cultivated freshwater fish in the World. However, there are still many undetermined phylogenetic relationships and the origins of common goldfish lineages, which are an obstacle to the conservation and genetic reproduction of this species. In the process of phylogenetic analysis, researchers used mitochondrial genomes where the genomic DNA was obtained from homozygous double haploid clonal lines from domesticated Songpu strains, and the total genomic DNA was extracted and sequenced using next-generation sequencing technology. Complete mitochondrial genome sequencing of 11 individuals representing East Asia and Europe and phylogenetic analysis was performed. The purpose of this study is to provide information about the phenology of Cyprinus carpio fish, which is expected to be the basis for increasing understanding to determine the kinship relationship between Cyprinus carpio in East Asia and Europe. The results showed that the relationship between Cyprinus carpio color, Cyprinus carpio songpu mirror carp, Cyprinus carpio carpio, and Cyprinus carpio wuyuanensis was very close, this can be seen from the bootstrap value of 100%. Meanwhile, with Cyprinus carpio haematopterus has a bootstrap value of 70%. Meanwhile, with Cyprinus xingguonensis it has a bootstrap value of 66%. Furthermore, it can also be said that the Songpu mirror goldfish is closely related to C. carpio carpio which is also a member of the genus Cyprinu. The genus Cyprinu has a close relationship with the genus Catla. In the phylogenetic tree, this species of fish forms a very coherent group, supported by a high bootstrap value of 100% and an average genetic distance of 0.02.  Key words: Mitochondrial genome, Phylogenetics, general Cyprinus carpio